Follicular dynamics and in vitro embryio production after repeated superovulation with FSH_P in Simmental heifers - Getz, Iva (Array, 2005)
Ultrasound transvaginal ovum pick-up was perofmed in 6 Simmental heifers aged between 14 and 18 month. The results show that the repeated FSH stimulation prior to ovum pick-up does not affect the follicular dynamic and developmental competence of bovine oocytes in Simmental heifers.